Correction: Sox-2 Positive Neural Progenitors in the Primate Striatum Undergo Dynamic Changes after Dopamine Denervation. - Cristina Ordoñez; Paz Moreno-Murciano; Maria Hernandez; Carla Di Caudo; Iñaki-Carril Mundiñano; Nerea Vazquez; Jose Manuel Garcia-Verdugo; Rosario Sanchez-Pernaute; Maria-Rosario Luquin (PLoS ONE, 2013)
[This corrects the article on p. e66377 in vol. 8.].